2007
DOI: 10.1007/bf03022027
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal pressure regulated volume assist ventilation in acute respiratory failure

Abstract: Purpose: Proportional assist ventilation (PAV) uses volume assist (VAV) and flow assist ventilation (FAV) to reduce elastic and resistive effort, respectively. Proportional assist ventilation may be difficult to apply clinically, particularly due to FAV related considerations. It was hypothesized that regulating tracheal (Ptr) rather than airway opening pressure (Pao), to overcome endotracheal tube related resistive effort, during VAV would provide an effective alternative method of ventilation. We therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
2

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…This is illustrated in Figure 1 of Mirkovic's paper: panel A showing the inspiratory effort (partitioned into its components) of a typical patient with airway opening pressure regulation (left) and with tracheal pressure regulation (right), panel B showing the ventilator assistance provided by VAV with the same two regulation systems. 9 Unsurprisingly, VAV progressively reduced the patients' elastic effort with increasing level of assistance. More interestingly, tracheal pressure regulated ventilation provided an important assistance against resistive loads compared with the conventional system (airway opening pressure regulation).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…This is illustrated in Figure 1 of Mirkovic's paper: panel A showing the inspiratory effort (partitioned into its components) of a typical patient with airway opening pressure regulation (left) and with tracheal pressure regulation (right), panel B showing the ventilator assistance provided by VAV with the same two regulation systems. 9 Unsurprisingly, VAV progressively reduced the patients' elastic effort with increasing level of assistance. More interestingly, tracheal pressure regulated ventilation provided an important assistance against resistive loads compared with the conventional system (airway opening pressure regulation).…”
mentioning
confidence: 98%
“…8 In a study reported in this issue of the Journal, Mirkovic et al address some of these issues with the implementation of PAV in the clinical setting, bringing two modifications to the conventional PAV system. 9 First, they used a simplified version of PAV, volume assist ventilation (VAV), providing assistance solely for the elastic component of the respiratory system impedance without any assistance for the resis- tive component. Secondly, they moved the site of airway pressure measurement from the Y-piece of the breathing circuit to the distal end of the tracheal tube.…”
mentioning
confidence: 99%
See 2 more Smart Citations